Population growth and environmental deterioration: An intertemporal perspective - Frank Jöst; Martin Quaas; Johannes Schiller (University of Heidelberg, Department of Economics, 2004)
Population growth is often viewed as a most oppressive global problem with respect to environmental deterioration. In this paper, we investigate the optimal development of a coupled system comprising population, economy, and the natural environment as subsystems. In our formal dynamic model these are interrelated by the society's economic decisions on consumption, birthrate, and emissions. Considering Hicks neutral technical progress, we find a steady state with growing population and declining per capita emissions, all other variables remaining constant over time. We investigate the comparative static properties of the steady state, and the dynamic behavior of the system. In numerical simulations we show that simple variations in the dynamics of the subsystems lead to complex and sometimes qualitatively different behavior of the coupled system. This is a challenge for policy advice based on such inter-temporal optimization models.
Keywords: J19; O13; Q25; 330; Sustainability; Economic Development; Endogenous Fertility; Bevölkerungsökonomik; Umweltökonomik; Familienökonomik; Haushaltsökonomik; Intertemporale Entscheidung; Neoklassisches Wachstumsmodell; Nachhaltige Entwicklung; Theorie